2022
DOI: 10.3390/nu14040832
|View full text |Cite
|
Sign up to set email alerts
|

Global, Regional, and National Estimates of Nutritional Deficiency Burden among Reproductive Women from 2010 to 2019

Abstract: Women of reproductive age (15–49 years) are often considered a vulnerable population affected by nutritional deficiencies, impairing their health and that of their offspring. We briefly introduced (a) the incidence and disability-adjusted life years (DALYs) trends from 2010 to 2019 and (b) the correlation between sex differences and income levels and nutritional deficiencies of reproductive women firstly. Notably, the burden of overall nutritional deficiencies among reproductive women remained generally stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It was ranked as the most challenging country for mothers and had the highest rate of deaths among children under the age of 5 years globally ( 29 ), which is consistent with the results of this study. Due to crises of conflict-related and widespread drought over the past 30 years, maternal and neonatal healthcare in Somalia was facing a serious healthcare crisis ( 30 , 31 ). With such a background, local health authorities in Somalia were facing the dual burden of rebuilding the healthcare system and handling urgent public health events resulting from continuing instability, conflicts, and natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…It was ranked as the most challenging country for mothers and had the highest rate of deaths among children under the age of 5 years globally ( 29 ), which is consistent with the results of this study. Due to crises of conflict-related and widespread drought over the past 30 years, maternal and neonatal healthcare in Somalia was facing a serious healthcare crisis ( 30 , 31 ). With such a background, local health authorities in Somalia were facing the dual burden of rebuilding the healthcare system and handling urgent public health events resulting from continuing instability, conflicts, and natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Although no prior research has specifically examined the burden of VAD in MENA, several global (7,16) and national (17)(18)(19)(20)(21)(22)(23) studies have been published. In 2019, one study reported the prevalence of micronutrient deficiencies and non-essential heavy metal levels in adults living in Saudi Arabia (17).…”
Section: Discussionmentioning
confidence: 99%
“…(5)(6)(7) However, maternal nutritional deficiency is a global public health problem that contributes to the death of 3.5 million women annually, mainly in low-and middle-income countries. (8,9) Africa has significantly higher undernutrition in pregnancy, and sub-Saharan Africa is the most affected region. (10)(11)(12) Ethiopia is the country where the undernutrition problem is still among the major health problems, especially among children and mothers, with a higher prevalence.…”
Section: Introductionmentioning
confidence: 99%